Удосконалений генератор з регульованою електричною напругою імпульсу на лінії електроогорожі для пасовищного утримання овець - Парієв, А. О.; Коротченко, Т. М.; Болтянський, Борис Володимирович; Болтянский, Борис Владимирович; Boltianskyi, Borys (ТДАТУ, 2020)
UK: Розроблення і виробництво електроогорожі для пасовищного утримання худоби та генератора високовольтних імпульсів, який ефективно відлякує тварин від огородженого периметру загону, дозволяє раціонально використовувати травостій при загінній пастьбі та збільшити продуктивність тварин порівняно з вільним випасом без огородження. Новий генератор високовольтних імпульсів має підвищену напругу імпульсу (5–7 кВ) для посушливих природних умов півдня України без зростання його потужності, що дозволяє пробивати вовну вівці та відлякувати тварин від огорожі. Генератор має значно зменшену потужність споживання за рахунок очікувального режиму і тому значно більший час роботи від акумулятора в автономних умовах на пасовищі – до 170 днів проти 30 днів в автоматичному режимі. За допомогою електроогорожі забезпечується механізація процесу випасання ВРХ і овець на пасовищі. Електроогорожа замінює працю пастуха та імпортне устаткування аналогічного призначення. Перспективність технічних засобів обумовлюється раціональним використанням зеленого корму, значним зниженням витрат і підвищенням продуктивності пасовища, забезпеченням тривалої автономної роботи електроогорожі на пасовищі без зв’язку з мережею струму. RU: Разработка и производство электроизгороди для пастбищного содержания скота и генератора высоковольтных импульсов, который эффективно отпугивает животных от огороженного периметра загона, что позволяет рационально использовать травостой при огражденном выпасе и увеличить продуктивность животных по сравнению со свободным выпасом без ограждения. Новый генератор высоковольтных импульсов имеет повышенное напряжение импульса (5–7 кВ) для засушливых природных условий юга Украины без роста его мощности, что позволяет пробивать шерсть овцы и отпугивать животных от ограждения.Генератор имеет значительно уменьшенную мощность потребления за счет выжидающего режима и поэтому значительно большее время работы от аккумулятора в автономных условиях на пастбище – до 170 дней против 30 дней в автоматическом режиме. С помощью электроизгороди обеспечиваетсямеханизация процесса выпаса КРС и овец на пастбище. Электроизгородь заменяет труд пастуха и импортное оборудование аналогичного назначения. Перспективность технических средств определяется рациональным использованием зеленого корма, значительным снижением затрат и повышением производительности пастбища, обеспечением длительной автономной работы электроизгороди на пастбище без связи с сетью тока. EN: The transition to year-round low-cost industrial production of meat and dairy products, including cattle and sheep, is impossible without the organization and introduction into the production of small mobile technical means for keeping cattle and sheep in cultivated pastures. Since the domestic industry does not produce specialized equipment for such purposes, it uses imported equipment that has a low pulse voltage (2–3 kV), which is not enough for arid climates of Ukraine, high power consumption and high price. Development and production of an electric fence for pasture keeping of cattle and a generator of high-voltage pulses, which effectively scares away animals from the fenced perimeter of the unit, allows rational use of grass during grazing and increase animal productivity compared to free grazing without fencing. The new high-voltage pulse generator has an increased pulse voltage (5–7 kV) for arid natural conditions in the south of Ukraine without increasing its power, which allows you to pierce sheep's wool and scare away animals from the fence. The generator has a significantly reduced power consumption due to standby mode and therefore much longer battery life in autonomous conditions on pasture – up to 170 days against 30 days in automatic mode. By means of an electric fence mechanization of process is provided grazing cattle and sheep on pasture. The electric fence replaces the work of the shepherd and imported equipment for similar purposes. The prospects of technical means are determined by the rational use of green fodder, a significant reduction in costs and increased productivity of the pasture, ensuring long-term autonomous operation of the electric fence on the pasture without connection to the mains.
Усовершенствованный генератор с регулируемым электрическим напряжением импульса на линии электроизгороди для пастбищного содержания овец
Advanced adjustable generator electric pulse voltage on the line electric fences for shepherd
Keywords: вівчарство; пасовища; генератор; електроогорожа; імпульс; напруга; овцеводство; пастбища; генератор; электроизгородь; импульс; напряжение; sheep breeding; pastures; generator; electric fence; impulse; voltage